Women's higher brain metabolic rate compensates for early Alzheimer's pathology - Erin E. Sundermann; Pauline M. Maki; Sarah Reddy; Mark W. Bondi; Anat Biegon; for the Alzheimer's Disease Neuroimaging Initiative (Alzheimer’s & Dementia: Diagnosis, Assessment & Disease Monitoring, 2020)
Abstract Introduction: The female advantage in brain metabolic function may confer cognitive resilience against Alzheimer's disease (AD). Methods: A total of 1259 participants (44% women; 52% mild cognitive impairment; 18% AD) aged 55 to 90 from the Alzheimer's Disease Neuroimaging Initiative (ANDI) completed tests of global cognition, verbal memory, and executive function, and neuroimaging assessments of regional glucose metabolism, hippocampal volume (HV), and amyloid beta (Aβ). We examined sex differences in brain metabolism and cognition by AD biomarker quartiles (Aβ, HV). We then examined if metabolism mediates sex differences in cognition. Results: Metabolism was higher in women versus men when pathology was mild‐to‐moderate (quartiles 2 to 3). Women outperformed men on all cognitive outcomes at ≥1 biomarker quartile, reflecting minimal‐to‐moderate pathology; however, these differences were eliminated/attenuated after adjusting for metabolism. The female advantage in verbal memory was also observed at minimal pathology quartiles but was unchanged after metabolism adjustment. Discussion: Women's greater brain metabolism may confer cognitive resilience against early AD.